Legion of super heroes. Volume 3 [videorecording (DVD)] / Kids WB. (Distributed by Warner Home Video, 2008)
With the help of teen heroes Bouncing Boy, Brainiac 5, Saturn Girl, and Lighting Lad, Clark Kent time-travels to the 31st century and fulfills his destiny as Superman. Includes 5 action-packed episodes from the first season.